Impact of COVID-19 Pandemic Lockdown on Oral Hygiene Practices and Willingness to utilize Dental Services among Patient Attendees of a Primary Oral Health Care Clinic in Ibadan, Nigeria - S.J. Akinloye; I.F. Sopeju; C.U. Akinloye; K.T. Adegoke; F.B. Lawal (Nigerian Dental Association, 2021)
Objective: To assess the impact of the COVID-19 pandemic lockdown on oral hygiene practices and willingness to utilize dental care services among patients who attended a Primary Oral Health Care Clinic in Ibadan, Nigeria. Materials and Methods: A cross-sectional study was conducted among 105 dental patients who had attended the Primary Oral Health Care Centre, Idikan, Ibadan, between July 2019 and March 2020. Data were obtained on the effect of COVID-19 pandemic lockdown on oral hygiene practices and willingness to utilise dental care services during the lockdown was obtained using semi structured questions. The questionnaire was administered through mobile telephone interviews by trained dentists. Data was analysed with SPSS version 25. Results: The mean age of the participants was 38.2 (±19.4) years, and 60 (57.1%) were females. During the COVID-19 pandemic lockdown, 19 (18.1%) of the participants reported a change in their oral hygiene habits, out of which 15 (14.3%) increased the frequency and duration of tooth cleaning while it reduced for 4 (3.8%) participants. Twenty-eight (26.7%) of the participants would not have considered visiting the dental clinic for routine check-ups during the period. Fear of contracting COVID-19 infection was the main reason for the unwillingness to utilize dental services for: routine check-up (15.7%) and oral prophylaxis (8.6%). There was no significant association between sociodemographic characteristics of the participants and change in oral health practices during the COVID-19 pandemic lockdown (p > 0.005). Conclusion: The impact of the COVID-19 pandemic was minimal on the oral hygiene practices of the study participants, with many having no change in their oral hygiene practices. The change in oral hygiene practices was in terms of frequency and duration of teeth cleaning. While some had a positive change, few others had negative changes.